Transcending the Institutionalist- Interpretivist Binary: Realizing Critical Realist Theory of Governance as Metagovernance - UNGSUCHAVAL, THEERAPAT (Universitas Muhammadiyah Yogyakarta, 2016)
Governance is essentially a popular contested concept and its definition is variously applied. Hence, it has arisen as a new mode by which society is governed and denotes the institutions, traditions and processes which define how power is operated. Given that, different governance scholars do have different ontological and epistemological positions. Two authoritative governance research strands have been noted: formal and institutional, and interpretive. The institutionalist approach assumes the capacity to understand governance through the behavior of institutions and organizations while the interpretative approach argues for the interpretations of individuals instead. However, this paper contends that both of them are commonly represented in binary and lack critical elements. This article thus tries to discuss the epistemological route to ‘transcend the institutionalist-interpretivist binary’ by specifying critical realist insights, which can contribute a relatively new perspective to governance research as the concept by nature is non-intradisciplinary and, in reality, holding a mixture of various modes and levels of governance. The alternative approach is the analytic of metagovernance. Metagovernance shows us an alternate way we can read contemporary governance which is, in particular, interested in power relations and interactive modes of governance, attempting to bring the centrality of the state back in the analysis of governance and then to call for the recognition of government and governance in the shadow of hierarchy. It sensitizes us the context and limits of governance rather than simply talking about the implications of the shift to governance with and through networks.